PELATIHAN ECOENZYM DAN BIOPORI SEBAGAI ALTERNATIF P5 YANG BERORIENTASI PADA SUSTAINABLE DEVELOPMENT GOALS DI SMA MUHAMMADIYAH PEKALONGAN - Fitri Palupi Kusumawati; Nurul Farida; Achyani Subadi (SINAR SANG SURYA, 2024)
This project aims to increase students' understanding of Pancasila values and encourage the implementation of the concept of Sustainable Development Goals (SDGs) in the school environment. The method for implementing the service program is carried out through four main stages. The planning stage includes notification and permission to partner schools, technical coordination, and socialization of waste utilization. Next are the implementation stage, evaluation stage and reflection stage.This program succeeded in increasing the understanding and skills of class X students in processing organic waste through making ecoenzymes and biopores. The activities carried out between March and May 2024 involve intensive outreach, training and mentoring by a team of service members and students from various study programs. Evaluation shows that most students have a good understanding of materials, manufacturing processes, and the benefits of ecoenzymes and biopores. The average score for students' understanding of ecoenzymes reached 87.06, while their understanding of biopores was 84.80. These results show the effectiveness of demonstration and practice methods in increasing students' awareness of organic waste management and supporting SDGs goals. Students also showed high enthusiasm in carrying out this project, which has the potential to be implemented as a sustainable lifestyle.